PENATALAKSANAAN PEMBERIAN ANESTESI LOKAL PADA GIGI ANAK - Sjahril Noerdin (Faculty of Dentistry, Universitas Indonesia, 2015)
Local anesthetics can at times pose quite a psychological hazard for children because they cannot tolerate pain and fear. Giving good dental treatments without pain and simultaneously giving cofort and relaxation is the responsibility of the dentist. Getting rid of the pain is not only important for the child but also for the dentist. In this way the dentist will be able to treat the child calmly without causing undue pain. Overcoming these problems involves one's need to have a high regard for children, a thorough understanding of their behavior patterns, and the ability to move fast and efficiently in administering anesthetic. Anticipating that his technique may not be successful created confusion in the child's mind, causing the whole visit to be a failure for himself, the child and the parent. Administering local anesthetics for children should be fast but simple and efficient. The use of syringes with needles of a correct size plus an adequate dose of anestheticum adiministered with the help of a dilligent and well motivated dental assistant will bring comfort. Without a good teamwork of the dentist and his dental assistant, it will be difficult to achieve a good administration of local anesthetics in children.